2007
DOI: 10.1007/s00213-007-0873-1
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine self-administration improves performance in a highly demanding water maze task

Abstract: Our data suggest that cocaine self-administration facilitates learning and memory in the water maze test only when animals are submitted to highly demanding tasks, involving working memory or consolidation-like processes during the intertrial interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…2006) demonstrated that cocaine self‐administration affects long‐term potentiating (LTP) but does not notably affect performance in the Morris water maze test. In contrast to these findings, in a different study, results showed an improvement in the rats' performance in a difficult Morris water maze task following cocaine self‐administration (Del Olmo et al . 2007).…”
Section: Introductionmentioning
confidence: 65%
“…2006) demonstrated that cocaine self‐administration affects long‐term potentiating (LTP) but does not notably affect performance in the Morris water maze test. In contrast to these findings, in a different study, results showed an improvement in the rats' performance in a difficult Morris water maze task following cocaine self‐administration (Del Olmo et al . 2007).…”
Section: Introductionmentioning
confidence: 65%
“…It is important for the acquisition of new learning and for the strengthening of learned associations for later retrieval (Zola-Morgan and Squire 1990; Morris et al 2006). Using either a water maze task of spatial learning (Del Olmo et al 2007) or a radial-arm maze task of spatial learning (Kantak et al 2005), adult rats self-administering cocaine or receiving it passively in a yoked fashion were shown to reach their goal (finding a hidden platform or retrieving all eight rewards) more quickly than saline controls when tested 0.5 to 3 hr after cocaine sessions ended. It is possible that these findings are explained by the psychomotor stimulant effects of cocaine and do not reflect an actual improvement in spatial learning.…”
Section: Neurocognitive Deficits Associated With Abused Substancesmentioning
confidence: 99%
“…Dose may be a critical factor for observing cocaine-induced improvements or deficits in spatial learning in rats because in the i.v. cocaine studies mentioned above (Del Olmo et al 2007; Kantak et al 2005), the cumulative dose of cocaine was approximately 10 to 15 mg/kg/day, with its i.v. delivery spaced over a 2-hr period.…”
Section: Neurocognitive Deficits Associated With Abused Substancesmentioning
confidence: 99%
“…), and at the behavioral level with the improved performance of LEW rats in the Morris water maze after cocaine self‐administration (Del Olmo et al . ).…”
Section: Discussionmentioning
confidence: 97%